Production of Volatile and Sulfur Compounds by 10 Saccharomyces cerevisiae Strains Inoculated in Trebbiano Must - Patrignani, Francesca; Chinnici, Fabio; Serrazanetti, Diana I.; Vernocchi, Pamela; Ndagijimana, Maurice; Riponi, Claudio; Lanciotti, Rosalba (Frontiers in Microbiology, 2016)
In wines, the presence of sulphur compounds is the resulting of several contributions among which yeast metabolism. The characterization of the starter Saccharomyces cerevisiae needs to be performed also taking into account this ability even if evaluated together with the overall metabolic profile. In this perspective, principal aim of this experimental research was the evaluation of the volatile profiles, throughout GC/MS technique coupled with solid phase micro extraction, of wines obtained throughout the fermentation of 10 strains of Saccharomyces cerevisiae. In addition, the production of sulphur compounds was further evaluated by using a gas-chromatograph coupled with a Flame Photometric Detector. Specifically, the ten strains were inoculated in Trebbiano musts and the fermentations were monitored for 19 days. In the produced wines, volatile and sulphur compounds as well as amino acid concentrations were investigated. Also the physico-chemical characteristics of the wines and their electronic nose profiles were evaluated.